Strategi Branding Kopi Sebagai Pemasaran Pariwisata Lembah Colol - Setia, Hilaria Ichaina; Vitrianto, Primantoro Nur; Isdarmanto (Universitas Pendidikan Ganesha, 2025)
This study analyzes the branding strategy of Colol coffee as a flagship product in the marketing of agrotourism in Lembah Colol, East Manggarai, East Nusa Tenggara. With strong geographical potential and rich local culture, several brands such as Ponan Coffee, Kopi Po’ong, and Kopi Tuk have emerged. The research employs a descriptive qualitative method through observation, interviews, and documentation. The findings indicate that the branding strategies include brand identity development, product positioning as a local symbol, and limited digital promotion. The main challenges include inadequate infrastructure, suboptimal promotion, and low community involvement. This study provides theoretical contributions and practical recommendations for the sustainable development of agrotourism through the strengthening of local coffee branding.